Evaluation of the quality of life of men undergoing stationary cardiac rehabilitation - Bielawa, Łukasz; Prusik, Katarzyna; Kortas, Jakub; Ossowski, Zbigniew; Prusik, Krzysztof; Konieczna, Seweryna; Wiech, Monika (Journal of Education, Health and Sport, 2017)
The aim of the study is to assess the quality of life of patients undergoing cardiac rehabilitation. Evaluation were subjected to 27 men in the Division of Cardiac Rehabilitation Wieżyca in 2014. Stay patients lasted from two to five weeks. The test using the questionnaire evaluating the quality of life of SF-36 was performed twice - at the beginning and end of the cycle rehabilitation.By analyzing and comparing the results between patients we concluded that comprehensive cardiac rehabilitation can significantly raise the performance quality of life in all its aspects. The largest increase in the value of quality of life was reported in the area of physical health. Obesity and smoking was accompanied by a significant part of the study group. On this basis, it can be said that these two risk factors for heart disease also reduce the quality of life of patients. Cardiac rehabilitation can reduce the risk of developing depression due to poor health. The effects of rehabilitation are greatest in patients after heart attacks. It can be presumed that the cause of this phenomenon is the minimally invasive treatment of the acute phase of the disease as compared with other cardiovascular diseases, for example. CABG, the heart valve prosthesis implantation. It has been observed relationship in which younger patients achieved better results in the area of physical health, but older people more has improved mental health. Based on the research it can be stated that a comprehensive cardiac rehabilitation is needed after the improvement of the quality of life of people with heart disease.